2022
DOI: 10.3390/ijms23116041
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Circulating MicroRNAs in XELOX-Chemotherapy-Induced Peripheral Neuropathy in Patients with Advanced Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common cancers and a leading cause of cancer deaths around the world. Chemotherapy is one of the most effective treatments for cancer patients, and has remarkably enhanced survival rates. However, it has many side effects. Recently, microRNAs (miRNAs) have been intensively studied as potential biomarkers for cancer diagnosis and treatment monitoring. However, definitive biomarkers in chemotherapy-induced peripheral neuropathy (CIPN) are still lacking. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…98 Additionally, blood-based biomarkers as indicators of CIPN severity would be beneficial both diagnostically and for the assessment of neuroprotectants. In both preclinical and clinical settings, a number of studies have suggested that neurotrophic nerve growth factor (NGF) 99,100 and microRNAs 101,102 may be valid markers. Of interest, preclinical studies indicate mitochondrial DNA (mtDNA) may be a useful early biomarker, 103 whilst clinical studies have indicated that brainderived neurotrophic factor (BDNF), [104][105][106] and various other agents such as circulating sphingosine-1-phosphate (S1P) might be candidates.…”
Section: Pathological Assessments With Preclinical and Clinical Relev...mentioning
confidence: 99%
“…98 Additionally, blood-based biomarkers as indicators of CIPN severity would be beneficial both diagnostically and for the assessment of neuroprotectants. In both preclinical and clinical settings, a number of studies have suggested that neurotrophic nerve growth factor (NGF) 99,100 and microRNAs 101,102 may be valid markers. Of interest, preclinical studies indicate mitochondrial DNA (mtDNA) may be a useful early biomarker, 103 whilst clinical studies have indicated that brainderived neurotrophic factor (BDNF), [104][105][106] and various other agents such as circulating sphingosine-1-phosphate (S1P) might be candidates.…”
Section: Pathological Assessments With Preclinical and Clinical Relev...mentioning
confidence: 99%